Microbiological Quality Control for Laboratory Rodents and Lagomorphs - Shek, William R. (Laboratory Animal Medicine, 2015)
Mice (Mus musculus), rats (Rattus norvegicus), other rodent species, and domestic rabbits (Oryctolagus cuniculus) have been used in research for over 100 years. During the first half of the 20th century, microbiological quality control of lab animals was at best rudimentary as colonies were conventionally housed and little or no diagnostic testing was done. Hence, animal studies were often curtailed and confounded by infectious disease (Mobraaten and Sharp, 1999; Morse, 2007; Weisbroth, 1999). By the 1950s, it became apparent to veterinarians in the nascent field of comparative medicine that disease-free animals suitable for research could not be produced by standard veterinary disease control measures (e.g., improved sanitation and nutrition, antimicrobial treatments) in conventional facilities. Henry Foster, the veterinarian who founded Charles River Breeding Laboratories in 1948 and a pioneer in the large-scale production of laboratory rodents, stated in a seminar presented at the 30th anniversary of AALAS, “After a variety of frustrating health-related problems, it was decided that a major change in the company’s philosophy was required and an entirely different approach was essential”. Consequently, he and others developed innovative biosecurity systems to eliminate and exclude pathogens (Allen, 1999). In 1958, Foster reported on the Cesarean-originated barrier-sustained (COBS) process for the large-scale production of specific pathogen-free (SPF) laboratory rodents (Foster, 1958). To eliminate horizontally transmitted pathogens, a hysterectomy was performed on a near-term dam from a contaminated or conventionally housed colony. The gravid uterus was pulled through a disinfectant solution into a sterile flexible film isolator where the pups were removed from the uterus and suckled on axenic (i.e., germ-free) foster dams. After being mated to expand their number and associated with a cocktail of nonpathogenic bacteria to normalize their physiology and prime their immune system, rederived rodents were transferred to so-called barrier rooms for large-scale production. The room-level barrier to adventitious infection entailed disinfection of the room, equipment, and supplies, limiting access to trained and properly gowned personnel, and the application of new technologies such as high-efficiency particulate air-filtration of incoming air (Dubos and Schaedler, 1960; Foster, 1980; Schaedler and Orcutt, 1983; Trexler and Orcutt, 1999). The axenic and associated rodents mentioned in the COBS process are collectively classified as gnotobiotic to indicate that they have a completely known microflora. By contrast, barrier-reared rodent colonies are not gnotobiotic because they are housed in uncovered cages and thus acquire a complex microflora from the environment, supplies, personnel, and other sources. Instead, they are described as SPF to indicate that according to laboratory testing, they are free from infection with a defined list of infectious agents, commonly known as an ‘exclusion’ list.